French-Polish lexicographical description of the <smells> object class for the purposes of machine translation. Additional studies - Hrabia, Michał (Papers in Linguistics, 2022)
This paper is a continuation of studies on the construction of French-Polish lexicographical description of olfactory perception nouns for the purpose of potential application in machine translation. The methodology of the conducted research derives from Wiesław Banyś’s object-oriented approach and the notion of object class, understood as a set of nouns characterized by a group of operations (verbs) and attributes (adjectives) specific to them. In the previous work (Hrabia 2019), the operations of the <smells> object class were analysed; in the present article, the focus is put on the attributes. Thanks to the analysis based on the frTenTen17 corpus, 76 attributes typical of the examined nouns, i.e. odeur, parfum, arôme, puanteur and senteur, were identified. In addition, it was shown that the <smells> class is not homogeneous and it does not form a hierarchical structure with the smaller classes that it consists of. The last part of the article presents a bilingual lexicographical “flashcard,” which is one of the description formats used in the objectoriented approach.